2012
DOI: 10.1002/jsfa.5658
|View full text |Cite
|
Sign up to set email alerts
|

The age of cows as a factor shaping the antioxidant level during a nutritional experiment with fish oil and linseed supplementation for increasing the antioxidant value of milk

Abstract: Modification of the diet of cows with fish oil and linseed significantly influenced antioxidant properties of their milk; however, the response of multiparous and primaparous cows was noticeably different to the supplement introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…Many factors affect the FA composition of bovine milk, including season (Sakowski and others ), parity (Puppel and others ), access to fresh grazing (Kuczyńska ; Kuczyńska and others ), grazing sward type (Hauswirth and other ), silage type (Dewhurst and others ), polymorphic forms of β‐lactoglobuline (Puppel and others ) or fish oil, and linseed supplementation (Puppel and others , ). Our study showed that the content of monounsaturated fatty acids (MUFA) in milk fat was dependent largely on the concentration of PUFA, and to a lesser extent on the supply of MUFA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Many factors affect the FA composition of bovine milk, including season (Sakowski and others ), parity (Puppel and others ), access to fresh grazing (Kuczyńska ; Kuczyńska and others ), grazing sward type (Hauswirth and other ), silage type (Dewhurst and others ), polymorphic forms of β‐lactoglobuline (Puppel and others ) or fish oil, and linseed supplementation (Puppel and others , ). Our study showed that the content of monounsaturated fatty acids (MUFA) in milk fat was dependent largely on the concentration of PUFA, and to a lesser extent on the supply of MUFA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…*** P <0.001; ** P <0.01; * P <0.05; †: P <0.10; NS: P >0.10. phytosterols) of camelina seed (Budin et al, 1995;Zubr & Matthaus, 2002), which provide a better oxidative stability of PUFA in camelina oil than fish oil and other vegetable oils rich in PUFA (Ni Eidhin et al, 2011). An increase in the total antioxidant status was noted in the milk of cows whose diets were supplemented with fish oil and linseed (Puppel et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of NEFA in the liver result in the increased production of reactive oxygen species, decreased para ‐oxonase activity, and the onset of oxidative stress 25. Antioxidants help to defend the body against free radicals, and cow's milk contains a range of biologically active substances with antioxidant properties 15. Kuczyńska14 has shown that milk from the organic production system was characterised by a higher level of antioxidant ingredients, which protect against peroxidation of NEFA.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of fat‐soluble vitamins was performed according to the methodology of Puppel et al 15. Separations were performed at ambient temperature, using a Zorbax Eclipse XDB C8 column.…”
Section: Experimental Designmentioning
confidence: 99%